Development of β-Lactamase as a Tool for Monitoring Conditional Gene Expression by a Tetracycline-Riboswitch in Methanosarcina acetivorans. (20th January 2014) - Demolli, Shemsi; Geist, Miriam M.; Weigand, Julia E.; Matschiavelli, Nicole; Suess, Beatrix; Rother, Michael
Abstract : The use of reporter gene fusions to assess cellular processes such as protein targeting and regulation of transcription or translation is established technology in archaeal, bacterial, and eukaryal genetics. Fluorescent proteins or enzymes resulting in chromogenic substrate turnover, like β -galactosidase, have been particularly useful for microscopic and screening purposes. However, application of such methodology is of limited use for strictly anaerobic organisms due to the requirement of molecular oxygen for chromophore formation or color development. We have developed β -lactamase from Escherichia coli (encoded by bla ) in conjunction with the chromogenic substrate nitrocefin into a reporter system usable under anaerobic conditions for the methanogenic archaeon Methanosarcina acetivorans . By using a signal peptide of a putative flagellin from M. acetivorans and different catabolic promoters, we could demonstrate growth substrate-dependent secretion of β -lactamase, facilitating its use in colony screening on agar plates. Furthermore, a series of fusions comprised of a constitutive promoter and sequences encoding variants of the synthetic tetracycline-responsive riboswitch (tc-RS) was created to characterize its influence on translation initiation in M. acetivorans . One tc-RS variant resulted in more than 11-fold tetracycline-dependent regulation of bla expression, which is in the range of regulation by naturally occurring riboswitches. Thus, tc-RS fusions represent the first solely cis -active, that is, factor-independent system for controlled gene expression in Archaea.